On the determination of the mechanical properties of wind turbine blades: Geometrical aspects of line based algorithms - Saravia, C. Martín; Gatti, Claudio D.; Ramirez, José M. (Renewable energy, 2017)
This paper discusses the aspects relating the geometric discretization of anisotropic wind turbine blade cross sections via line elements and the calculation of its mechanical properties. The geometrical reconstruction of the blade is done through an algorithm that reads a table that contains the representation of the aerodynamic profile of the blade as a set of connected line segments. The composite material theoretical background is based on a vector variant of the classical lamination theory embedded into a geometrically exact large deformation-small strain thin-walled beam formulation; transverse shear and out of plane warping effects are considered. The impact of the geometric reconstruction in the accuracy of the mechanical properties is studied using both rectangular and trapezoidal elements. It is found that a proper geometrical reconstruction of the cross section must be ensured to obtain small errors in the mechanical properties. It is shown that line based algorithms can give very accurate results provided the cross section geometry is adequately represented. •A line based formulation for structural modeling of composite wind turbine blades is presented.•The impact of the blade geometric modeling in the stiffness and mass parameters is studied.•A reconstruction scheme based on rectangular and trapezoidal elements is presented.•Several benchmark tests show that the formulation has excellent accuracy.